1998
DOI: 10.1002/(sici)1097-4628(19980523)68:8<1303::aid-app12>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Physicomechanical properties of filled natural rubber vulcanizates modified with phosphorylated cashew nut shell liquid

Abstract: Effect of fillers like carbon black, silica, and china clay on the cure characteristics and physicomechanical properties of natural rubber (NR) modified with phosphorylated cashew nut shell liquid (PCNSL) in various proportions has been studied. Prominent cure retardation has been observed with progressive increase in concentration of PCNSL from 0 to 20 phr. The softening effect of PCNSL on the vulcanizate has been displayed by the linear decrease in hardness and tensile modulus and the increase in elongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…Cashew nut shell liquid (CNSL) and its derivatives have long been used as rubber compounding additives in various roles such as plasticizers, antioxidants, and vulcanizate property modifiers . Menon et al studied cure characteristics and physicomechanical properties of NR vulcanizates modified with phosphorylated CNSL (PCNSL). PCNSL‐modified NR vulcanizates showed improved thermooxidative aging and decomposition, especially at the higher concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Cashew nut shell liquid (CNSL) and its derivatives have long been used as rubber compounding additives in various roles such as plasticizers, antioxidants, and vulcanizate property modifiers . Menon et al studied cure characteristics and physicomechanical properties of NR vulcanizates modified with phosphorylated CNSL (PCNSL). PCNSL‐modified NR vulcanizates showed improved thermooxidative aging and decomposition, especially at the higher concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Cardanol presents chemical and physical properties very close to those of DEHP. It is reported that properties of natural rubber (NR) modified with phosphorylated cardanol have been found to be superior to those obtained by DEHP [26]. Also, phosphorylated cardanol has been used as an effective plasticizer for ethyleneepropyleneediene rubber [27], polychloroprene and polybutadiene rubber [28], and LLDPE/EVA copolymer blends [29].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorus-modified CNSL prepolymer has been found to act as a multifunctional additive in NR in various roles. It can act as cross-linkable plasticizer, softener, tackifier, antidegradant and improver of thermal stability, improver of mechanical properties of vulcanizates, such astensile strength, tear strength and fatigue resistance, and coupling agent between filler and rubber [166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182]. Introducing free radical polymerizable moieties would enable cardanol to become a potential monomer for the molecular design of high-value polymers [183][184][185].…”
Section: 'Synthetically-inspired' Materials From Natural Monomersmentioning
confidence: 99%